Tingkat Pengetahuan Petani dalam Penggunaan Pupuk Organik dan Penerapannya pada Budidaya Tanaman Padi Sawah (Kasus di Subak Penarungan, Kecamatan Mengwi, Kabupaten Badung) - ARTAWAN, I WAYAN BUDI; ASTITI, NI WAYAN SRI; SUDARTA, WAYAN (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.6, No.4, Oktober 2017, 2017)
Farmers Knowledge Level in the Use of Organic Fertilizer and Its Application in Rice Cultivation (Case in Subak Penarungan, Sub-District of Mengwi, Badung Regency) Public attention to the issue of agriculture and the environment in recent years have increased as a result of a big negative impact on the environment, compared with its positive impact on increasing the productivity of agricultural crops. This encourages several regions to hold organic farming. Organic farming is a natural farming which in practice trying to avoid the use of chemicals and fertilizers that are poisoning the environment with the aim to obtain a healthy environmental condition.This study aims to determine (1) the level of farmers' knowledge on organic fertilizer; and (3) the application of organic fertilizers by the farmers in the cultivation of lowland rice. The research was conducted at the Subak of Penarungan, Mengwi Sub-District of Badung Regency. The choice of research location was conducted by purposive sampling. The population of the research was the active members of Subak of Penarungan totaling of 167 people. The sample size was determined by using the formula of Slovin, so that the number of respondents was 63 people.This research use method analysaize descriptive qualitative. The results showed that farmers' knowledge about organic fertilizers can be categorized in the high category with achieving a score of 3.41. However, the application of organic fertilizer by the farmers is classified in the medium category by achieving a score of 3.05. Based on the results of this study can be suggested farmers as actors should be more active doing weeding and want to optimize the use of organic fertilizer as recommended by the extension. Because the use of sustainable organic fertilizer for the future will give a big influence in soil fertility, quality and not damage the environment.